The psychological and social undermining of the personality in the texts of the world stage: The gorilla as a model - Salah Hamadi Jazaa; Hussan Abod Ali (Basrah Arts Journal, 2023)
The subject of undermining depended on many intellectual and philosophical systems, and it penetrated into most aspects of human life, such as political, social, cultural and artistic, to indicate the inconsistency of the human world, the disintegration of its parts, and the collapse of values. This concept refers to the human personality in its real and hypothetical capacity, as it was the plaything in the hands of these practices in order to pass its ideas, so the personality sometimes ascended the top of the pyramid and at other times descended towards the abyss, after it was lowered to the rank of an animal, and for the necessity of this topic, the researcher decided to formulate the title of his research, including A study of (psychological and social undermining of the personality in the texts of the high theater), because the global theater presented many models that were a witness to most of these practices that were applied against the personality throughout the ages, and the manifestations of demolition, distortion, loss and destruction that followed.